ZmERF21 directly regulates hormone signaling and stress‐responsive gene expression to influence drought tolerance in maize seedlings. (27th December 2021) - Wang, Zhiyong; Zhao, Xiang; Ren, Zhenzhen; Abou‐Elwafa, Salah Fatouh; Pu, Xiaoyu; Zhu, Yingfang; Dou, Dandan; Su, Huihui; Cheng, Haiyang; Liu, Zhixue; Chen, Yanhui; Wang, Ertao; et al.
Abstract: Drought stress adversely impacts crop development and yield. Maize frequently encounters drought stress during its life cycle. Improvement of drought tolerance is a priority of maize breeding programs. Here, we identified a novel transcription factor encoding gene, APETALA2 ( AP2 )/ Ethylene response factor (ERF), which is tightly associated with drought tolerance in maize seedlings. ZmERF21 is mainly expressed in the root and leaf and it can be highly induced by polyethylene glycol treatment. Genetic analysis showed that the zmerf21 mutant plants displayed a reduced drought tolerance phenotype, accompanied by phenotypical and physiological changes that are commonly observed in drought conditions. Overexpression of ZmERF21 in maize significantly increased the chlorophyll content and activities of antioxidant enzymes under drought conditions. RNA‐Seq and DNA affinity purification sequencing analysis further revealed that ZmERF21 may directly regulate the expression of genes related to hormone (ethylene, abscisic acid) and Ca signaling as well as other stress‐response genes through binding to the promoters of potential target genes. Our results thereby provided molecular evidence of ZmERF21 is involved in the drought stress response of maize. Summary Statement: Drought stress adversely destroys maize development during the whole life cycle, finally reducing its yield and quality. Thus, improving the performance of maize against drought tolerance is a priority of breeding programs. Here, we identified a novel transcription factor ZmERF21 that is tightly associated with drought tolerance in maize seedlings. ZmERF21 is mainly expressed in root and leaf. Mechanistic analysis demonstrated that ZmERF21 could directly bind to the genes involved in hormone (ethylene, abscisic acid) and Ca signaling pathways. Furthermore, overexpression of ZmERF21 in maize significantly increased drought tolerance, evidenced by chlorophyll content and the activities of antioxidant enzymes. Taken together, our results revealed that ZmERF21 is a positive regulator in response to drought stress in maize.